Malleable Penile Implant Is an Effective Therapeutic Option in Men With Peyronie's Disease and Erectile Dysfunction. Issue 1 (11th January 2018) - Habous, Mohamad; Tealab, Alaa; Farag, Mohammed; Soliman, Tarek; Williamson, Ben; Mahmoud, Saad; Elserafy, Amin; Mekawi, Zenhom; Remeah, Abdallah; Nassar, Mohammed; Laban, Osama; Abdelwahab, Osama; et al.
Abstract: Background: The inflatable penile prosthesis (IPP) is typically the preferred implant for Peyronie's disease (PD) and malleable penile prostheses (MPPs) have been discouraged. Aims: To evaluate the effectiveness and patient satisfaction of the MPP vs IPP in patients with PD. Methods: Men with PD and erectile dysfunction who elected for penile implant surgery constituted the study population. Preoperatively, demographic and comorbidity parameters were recorded. Curvature was measured with a goniometer at maximum rigidity after intracavernosal injection of a vasoactive agent. Postoperatively, overall satisfaction was measured at 3, 6, 12, and 24 months on 5-point Likert scale from 1 (dissatisfied) to 5 (very satisfied). Results: 166 men with a mean age of 59 ± 10 years were analyzed. The mean preoperative curvature in the entire cohort was 65° (range = 30–130°). 94% of patients with MPP had total resolution of their curvature at the end of the operation, whereas 8 patients (6%) had residual curvature (25–40°). In the IPP group 25 of 30 (83.3%) had a straight penis at the end of surgery, whereas 5 of 30 (16.7%) had residual curvature, with the mean magnitude being 33° in the MPP group and 30° in the IPP group. 86% of all patients had diabetes. There were no differences between the 2 implant groups in age, hemoglobin A1c, body mass index, or smoking status. The mean patient satisfaction was 4.42 ± 0.70 (range = 2–5) and there was no difference between the 2 groups. The mean follow-up period was 23.4 months (range = 6–29 months). Conclusion: We found that the MPP is as effective as the IPP in curvature correction in patients with PD, with similar patient satisfaction for the 2 groups.